Compromised Differentiation Potential of Diabetic Dental Pulp Stem Cells - Bhate, Kalyani; Kharat, Avinash; Kheur, Supriya; Sanap, Avinash; Bhonde, Ramesh; Gopalakrishnan, D. (Journal of Health and Allied Sciences NU, 2024)
Background Dental pulp-derived mesenchymal stem cells (DPSCs) are documented to be a promising source for the treatment of a diverse spectrum of diseases including type 2 diabetes mellitus (T2DM). However, alterations in the characteristics of DPSCs from the T2DM patients are still unclear.Objective The purpose of this study was to compare the characteristics of dental pulp stem cells obtained from diabetic and nondiabetic healthy individuals.Methods Dental pulp stem cells from nondiabetic (ND-DPSCs) and diabetic (D-DPSCs) were isolated by the explant culture method. Both cells were expanded in identical culture conditions and subsequently differentiated into osteogenic, chondrogenic, and adipogenic conditions. D-DPSCs and ND-DPSCs were characterized for a panel of MSCs-specific surface markers. Senescence associated with β-galactosidase was performed. In addition, we also performed an in vivo chick embryo yolk sac membrane assay for angiogenesis.Results Findings of this study showed that diabetes mellitus affected the osteogenic and chondrogenic differentiation, while adipogenic differentiation was significantly higher in D-DPSCs as compared to ND-DPSCs. Clonogenic ability and angiogenic potential of ND-DPSCs is higher than D-DPSCs despite similar surface marker expressions.Conclusion Diabetes affects the stemness of D-DPSCs in terms of clonogenic, osteogenic, and chondrogenic differentiation and angiogenic potential, reflecting the adverse effects of hyperglycemia even on dental pulp stem cells.
Keywords: angiogenesis; dental pulp stem cells; diabetes mellitus; differentiation; stemness